Monitoring the Clinical Evolution of A Psychotic Patient Presenting A First-Schizophrenic Episode Thanks to Bimodal Oddball-P300 Event-Related Potentials: First Evidence from A Single-Case Study - Kajosch, Hendrik; Hanard, Florence; Steegen, Geerke; Persefonis, Georgios; Cimochowska, Agnieszka; Michel, Steve; Kornreich, Charles; Campanella, Salvatore (Archives of Clinical and Medical Case Reports, 2020)
Objective: Previous studies showed that a bimodal oddball design allows to increase the sensitivity of the P300 in subjects with anxious-depressive tendencies and patients presenting an adjustment disorder. In this case report we illustrate the increased sensitivity of a bimodal oddball task in the clinical follow-up of a patient presenting a psychosis in the context of a first onset schizophrenia. Method: The patient was instructed to detect deviant stimuli in three separate oddball tasks by hitting a button. Tasks comprised an auditory, a visual and a synchronized and congruent audio-visual block of stimuli. The peak-latency and the amplitude of the P300 evoked response were compared and confronted to scores of the clinical assessment. Results: Only the bimodal task mirrored the clinical evolution of the patient, as the reduction of psychotic symptoms was accompanied by an increase of the bimodal P300 amplitude. However, this was not true for both unimodal tasks (auditory and visual). Conclusions: A bimodal oddball design combined with unimodal ones could be necessary to monitor the joined clinical/neurophysiological evolution of a patient presenting a first onset psychosis. Significance: Further longitudinal studies applying the bimodal P300 paradigm should be designed in order to verify whether the oddball-bimodal P300 component could be used as “state” and/ or “trait” biological marker of the disease.